Pengaruh Ukuran Font Running text Terhadap Arus Dan Hambatan - Fellian Helmi Pristianto; Untung Suryadhianto; Ratna Mustika Yasi (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2022)
Abstract - The purpose of this study was to determine the effect of running text font size on current and resistance. 1. The running text device, changing the information is often done using a PC (Personal Computer) so that it is not effective in implementing it. The role of the use of color from the display running text invites the eyes of the people around it to look at it. In addition to the color output, the selection of the font size and the use of letters or numbers is the main attraction of the running text display. At the trial stage of data collection, it can be seen that the font size of the running text affects the current and the resulting resistance..